In Vivo GFP Knockdown by Cationic Nanogel-siRNA Polyplexes - Shrivats, Arun R. (Bioengineering (Basel), 2015)
RNA interference (RNAi) is a powerful tool to treat diseases and elucidate target gene function. Prior to clinical implementation, however, challenges including the safe, efficient and targeted delivery of siRNA must be addressed. Here, we report cationic nanogel nanostructured polymers (NSPs) prepared by atom transfer radical polymerization (ATRP) for in vitro and in vivo siRNA delivery in mammalian models. Outcomes from siRNA protection studies suggested that nanogel NSPs reduce enzymatic degradation of siRNA within polyplexes. Further, the methylation of siRNA may enhance nuclease resistance without compromising gene knockdown potency. NSP-mediated RNAi treatments against Gapdh significantly reduced GAPDH enzyme activity in mammalian cell culture models supplemented with 10% serum. Moreover, nanogel NSP-mediated siRNA delivery significantly inhibited in vivo GFP expression in a mouse model. GFP knockdown was siRNA sequence-dependent and facilitated by nanogel NSP carriers. Continued testing of NSP/siRNA compositions in disease models may produce important new therapeutic options for patient care.